RANCANG BANGUN ALAT PELIPAT DAN PEWANGI BAJU OTOMATIS - Wahyu Fahrizal; Arin Yerliansyah; Novitasari, Novitasari; Yudhi (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Design a multifunction tool that includes a clothes folder and freshener. Additional features of this design are clothing sterilization with UV lamps and automatic calculations. This design aims to smooth and increase efficiency in the clothing care process. This tool is designed to provide a comprehensive solution for caring for everyday clothes quickly and effectively. This tool combines several main functions: first, an automatic folder that uses a mechanical system and sensors to precisely fold clothes of various types and sizes. Second, a fragrance feature that sprays a fresh aroma onto clothes after being folded, increasing freshness and comfort when used. Third, the sterilization system uses UV lights to kill germs and microorganisms that may be on clothes, maintaining user cleanliness and health. Finally, the automatic calculation feature controls the number of clothes processed and provides reports automatically to users. The tool is equipped with a smart user interface, allowing users to easily manage and monitor the clothing care process. With this multifunctional tool, it is hoped that it can reduce the time and energy needed to care for clothes and increase comfort and cleanliness for users. The results obtained are that design tools can provide tidiness, cleanliness and protect against bacteria. The range of folding clothes using the tool is 5 minutes.